The canon in the history of economics : critical essays - Psalidopoulos, M. (Michalēs) (Routledge studies in the history of economics, 2000)
This book represents the first critical attempt to incorporate the question of the canon in the history of economics into contemporary scholarly debate. It discusses how the canon is formed, perpetuated, interpreted and re-interpreted.